Usulan Pengembangan Bisnis UMKM dengan Pendekatan Analisa SWOT dan Business Model Canvas (BMC) - Khofiyah, Nida An; Windyatri, Hasyrani; Riandani, Andini Putri; Herol, Herol (Universitas Pahlawan Tuanku Tambusai, 2025)
This study explores the development of MSME businesses using SWOT analysis and the Business Model Canvas (BMC) approach. The primary focus is on creating innovative planner notebooks aimed at helping students, workers, and entrepreneurs manage their daily schedules and achieve their goals. The method used is the SWOT and BMC analysis approach. The results show that the product has a broad market potential, supported by marketing strategies through social media, e-commerce, and direct promotions. The unique value propositions include goal-setting consultations and monthly online mentoring. A break-even analysis indicates the business is expected to reach its break-even point after selling 404 units. This research emphasizes the importance of innovation in creating added value for MSME products to enhance market competitiveness